(untitled) (Ibrahim Medical College Journal, 2009)
Methods and materials - A rural community was purposively selected in Sreepur thana of which four villages were selected randomly. The total population of all age groups was 14,165 and the eligible reproductive aged females were 3,820 based on age between 15 and 45 years. Sample size was estimated at 573 (15%) of the eligible participants depending on the availability of time and logistic support. The study design was to use a questionnaire related to age, education, family income, housing and sanitation. Height (ht), weight (wt) and blood pressure (BP) were measured. Urine protein was estimated. Clinical examinations noted the presence of anemia, jaundice, edema, ring-worm, scabies, goiter, xerophthalmia and gum bleeding. Body mass index (BMI) was calculated to determine their obesity or wasting. Results - Overall, 501 volunteered and the response rate was 87.4%. Of these participants, 30.3% were illiterate. Almost all of them had supply of tube-well water and 68% had sanitary latrines. Their mean (±SD) age was 30.2 (±2.9)y, wt was 46 (±8.5)kg, ht was 149 (±5)cm and BMI was 20.5 (±3.5). The poor women had significantly lower BMI than the rich [20.0 (2.93) vs. 21.2 (4.1), (p<0.05)]. Their mean (±SD) systolic and diastolic blood pressure were 116 (±17) and 73 (±12) mmHg, respectively. The prevalence of hypertension, proteinuria and glycosuria were 16.6, 10.4 and 2.6%, respectively. The frequencies of proteinuria and ring-worm were significantly higher among the poor than among the rich social class (both cases p<0.05). Regarding nutritional deficiency, about half of the rural women (52%) had some form of signs relating to Vit-A deficiency and 65% had signs of Vit-B complex deficiency either in the form of glossitis or of angular stomatitis or both. Conclusions - Despite time and logistic constraint, the study revealed that most of the rural women had a poor nutritional status (80% had BMI<23.0). The prevalence of hypertension and glycosuria were also not negligible. Vitamin deficiency disorders (xerophthalmia), gum-bleeding, angular stomatitis were also very high among them. The study also revealed that the poor social class had a significantly lower BMI, higher proteinuria and higher skin problems than their rich counterparts. Ibrahim Med. Coll. J. 2008; 2(1): 21-24 Key Words: doi: 10.3329/imcj.v2i1.2927